2010
DOI: 10.3109/0142159x.2010.498488
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and its correlates in Iranian physicians: A preliminary psychometric study of the Jefferson Scale of Physician Empathy

Abstract: Background: Empathy is one of the fundamental factors in patient care that is beneficial to both patient and physician. Aims: To assess the psychometric properties of the Persian version of the Jefferson Scale of Physician Empathy (JSPE) in a sample of Iranian physicians and examine its correlates. Method: Two hundred and seven general physicians completed the JSPE. The associations of empathy scores with demographic characteristics and practice-related variables were examined. Results: The scale showed an acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 17 publications
2
49
4
Order By: Relevance
“…In exploratory factor analytic studies, three factors of ''perspective taking,'' ''compassionate care'' and ''walking in patients' shoes'' have emerged in samples of medical students and physicians in the United States (Hojat et al 2001a(Hojat et al , 2002c and abroad (Alcorta-Gaza et al 2005;Di Lillo et al 2009;Kataoka et al 2009;Rahimi-Madiseh et al 2010;Roh et al 2010;Shariat et al 2010). The three-factor model was also reproduced in confirmatory factor analytic studies with medical students in England (Tavakol et al 2011) and in medical students in Iran (Shariat & Habibi 2013).…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 94%
See 1 more Smart Citation
“…In exploratory factor analytic studies, three factors of ''perspective taking,'' ''compassionate care'' and ''walking in patients' shoes'' have emerged in samples of medical students and physicians in the United States (Hojat et al 2001a(Hojat et al , 2002c and abroad (Alcorta-Gaza et al 2005;Di Lillo et al 2009;Kataoka et al 2009;Rahimi-Madiseh et al 2010;Roh et al 2010;Shariat et al 2010). The three-factor model was also reproduced in confirmatory factor analytic studies with medical students in England (Tavakol et al 2011) and in medical students in Iran (Shariat & Habibi 2013).…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 94%
“…In addition, among consistent findings was the gender difference in mean scores of the JSE in the favor of female medical students (Hojat et al 2001a(Hojat et al , 2002a(Hojat et al , 2002b and in practicing physicians (Hojat et al 2002c) in the United States and abroad (Hsiao et al in press;Alcorta-Garza et al 2005;Kataoka et al 2009;Shariat et al 2010;Suh et al 2012;Zenasni et al 2012). This pattern of finding for women's higher empathy is consistent with those reported in the general population.…”
Section: E1279mentioning
confidence: 96%
“…Nevertheless, its psychometric properties such as validity and reliability must be proved and culturally adapted for the specific population of interest. The JSPE has been translated into 42 languages and recently these different versions were used for assessing empathy among American [9], English [8], Italian [11], Japanese [12], Mexican [13], French [14], German [15], Polish [16], Korean [17] and Iranian [18] physicians or medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from literature on the impact of years of practice experience in influencing empathy level is mixed. 22,[35][36][37][38][39] The lack of consistent results could be partly explained by the variability of the study participants (either interns or professionals) and the stage of professional practice. Two longitudinal studies among undergraduate medical and dental students found a decline in empathy level as the students progressed through their professional training.…”
Section: Discussionmentioning
confidence: 99%